2021
DOI: 10.1002/cam4.4273
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi for cancer survivors: A systematic review toward consensus‐based guidelines

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 93 publications
(259 reference statements)
0
10
0
3
Order By: Relevance
“…37 Additional studies are needed to evaluate whether the observed associations are causal, and if so, to develop theory-based interventions that can be incorporated into cancer survivorship care to reduce sedentary behavior and increase physical activity. 6,38…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Additional studies are needed to evaluate whether the observed associations are causal, and if so, to develop theory-based interventions that can be incorporated into cancer survivorship care to reduce sedentary behavior and increase physical activity. 6,38…”
Section: Discussionmentioning
confidence: 99%
“…Low LTPA and prolonged sitting may also contribute to increased risk of cachexia, thromboembolic events, and fatigue, which all influence survival after cancer . Additional studies are needed to evaluate whether the observed associations are causal, and if so, to develop theory-based interventions that can be incorporated into cancer survivorship care to reduce sedentary behavior and increase physical activity …”
Section: Discussionmentioning
confidence: 99%
“…While its definitive impact requires further extensive research, some studies suggest benefits such as enhanced physical functioning, stress reduction, improved mental health, immune enhancement, and improved quality of life, and that it may complement conventional medicine as adjunct therapy by providing a holistic approach to cancer care. 29 , 33 - 44 As research progresses, understanding its potential role in cancer medicine could open doors to more comprehensive and patient-centric approaches to healthcare. In this regard, GQ emerges as a unique mind-body exercise that combines moderate and adaptive walking exercise with a pronounced focus on a specialized breathing technique.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies have shown that mind-body exercise such as Qigong can reduce fatigue, improve sleep, depression, anxiety, quality of life and cognitive changes associated with cancer as well as biomarkers of stress, cortisol level, inflammation and immune function in cancer survivors during and after treatment. 29 , 33 - 44 …”
Section: Introductionmentioning
confidence: 99%
“…Since some patients may not be physically able to perform aerobic exercise or resistance training, Tai Chi, yoga, or Baduanjin exercises may be more feasible alternatives to suggest. A systematic review evaluating Tai Chi identified benefits for fatigue and sleep quality among cancer patients, but there was insufficient evidence on long term outcomes [10]. Another exercise option is also Baduanjin, a tradition Chinese Qigong exercise that consists of eight easy movements of the body, which in a systematic review and me-ta-analysis of randomized control trials, has been found to improve cancer fatigue, sleep, and quality of life among cancer patients [11].…”
Section: Tai Chi Yoga and Baduanjin As A Form Of Exercisementioning
confidence: 99%